2016
DOI: 10.1080/10494820.2016.1244084
|View full text |Cite
|
Sign up to set email alerts
|

Recommender system for learning SQL using hints

Abstract: Today's software industry requires individuals who are proficient in as many programming languages as possible. Structured query language (SQL), as an adopted standard, is no exception, as it is the most widely used query language to retrieve and manipulate data. However, the process of learning SQL turns out to be challenging. The need for a computer-aided solution to help users learn SQL and improve their proficiency is vital. In this study, we present a new approach to help users conceptualize basic buildin… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 30 publications
(38 reference statements)
0
7
0
Order By: Relevance
“…Previous studies have shown that there are challenges and difficulties in the learning of SQL [44,45,19,18]. To ensure considerable practice as proposed by [19], a formative assessment system should pre-assess students' prior learning before the start of a new learning, and where there are gaps, recommend materials for more practice.…”
Section: B Logic Based Rules Formalism For Classificationmentioning
confidence: 99%
“…Previous studies have shown that there are challenges and difficulties in the learning of SQL [44,45,19,18]. To ensure considerable practice as proposed by [19], a formative assessment system should pre-assess students' prior learning before the start of a new learning, and where there are gaps, recommend materials for more practice.…”
Section: B Logic Based Rules Formalism For Classificationmentioning
confidence: 99%
“…• Group 3: 33 learners. (Lavbič, Matek and Zrnec, 2017) propose a new approach to help users learn SQL easily. The analysis was performed on a database of 93 learners.…”
Section: Other Recommendation Systemsmentioning
confidence: 99%
“…As a possible teaching approach to database concepts, one could use intelligent tutoring systems and interactive learning environments such as [9,11,12,23,29,30], but since the aim of our study is to analyze learning outcomes for basic CLR concepts when using different notations, we did not elaborate on these approaches in detail.…”
Section: Related Workmentioning
confidence: 99%